Survey of medieval inscribed objects from Bergen: Items other than wooden sticks or pieces of wood - Zilmer, Kristel (Maal og Minne, 2020)
This survey is a supplementary resource to the article "Runic Sticks and Other Inscribed Objects from Medieval Bergen: Challenges and Possibilities" (see Maal og Minne 2020). The survey is based on investigations of the Bryggen corpus, carried out mainly in the years 2013-18.1 Own field notes and photographs have been complemented by information in runological or archaeological databases and publications (available per January 2020). The purpose behind the survey is twofold. For one, it demonstrates the variability of the corpus; it contains information on inscribed artefacts, which can be determined to represent something other than wooden sticks or pieces of wood. Secondly, the survey brings to the fore some of the interesting ambiguities in the study of inscribed artefacts, especially regarding wooden items. The table presents an overview of artefacts, which with some certainty can be identified as (parts of) sundry tools, vessels, implements and other functional objects. As such, they display alternative functionalities than primarily script-bear-ing objects. Artefacts made of materials other than wood are also included (marked in bold). The number of items may be subject to change depending upon the adjustment of classification criteria and the reassessment of individual objects.2 Uncertain instances regarding objects and their functions are indicated with question marks. The included descriptions on forms of writing (i.e. primary, secondary, and tertiary) follow the categories introduced by Franklin (2002) - presented in more detail in the article. Such assessments illuminate the diverse nature andÂ dynamic boundaries of the evidence; they do not work as rigid groups. With some inscribed artifacts, the form of writing also remains uncertain.